Experimento numérico sobre desempenho térmico estrutural de uma casa popular do Programa Minha Casa Minha Vida - DANTAS, Euley Johan da Silva (2023)
The social program My Home My Life is a federal government initiative whose main objective is to implement policies and programs that promote access to decent housing for the low-income population. In this paper, the standard popular housing project is used as a test case to simulate and numerically analyze its thermal performance, focusing on indoor air temperature and indoor relative humidity. The study aims to suggest improvements in thermal comfort. The numerical experiment is performed on climate data for the city of Belém-PA in the year 2022, to verify if the popular house complies with the thermal comfort standards according to NBR 16401-2. The results obtained for thermal comfort in the bathroom with the materials originating from the floor plan showed 510 hours of the year 2022, with the exchange of materials the thermal comfort reached 1,260 hours. In the front bedroom with the materials proposed by the floor plan the thermal comfort presented 2,160 hours, with the exchange of materials the thermal comfort reached 3,160 hours. In the back bedroom with the floor plan materials thermal comfort reached 2,340 hours, with the materials change thermal comfort reached 3,260 hours. In the living room and kitchen with the materials of the ground floor plan thermal comfort had 3,010 hours, with the exchange of materials the thermal comfort reached 3,820 hours.